Acetaminophen induced Stevens Johnson syndrome - Toxic Epidermal Necrolysis Overlap Syndrome: A rare Adverse Reaction - Kavthekar, Saiprasad Onkareshwar; Amith, K.; Bapurao Kurane, Anil; J Phulari, Yoganand (Journal of Nepal Paediatric Society, 2022)
Stevens Johnson syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are hyper sensitive life - threatening rare dermatological reactions. In SJS - TEN overlap syndrome, the extent and severity of epidermal detachment is 10- 30%. Drugs like sulfonamides, nonsteroidal anti- inflammatory agents, antibiotics and anticonvulsants are the commonest precipitants. Here, we present a rare case of SJS - TEN overlap syndrome in a previously normal 11 years old girl after acetaminophen intake for fever. This case report is intended to make paediatricians aware that the adverse reaction like SJS - TEN overlap syndrome can develop with a drug like acetaminophen which is supposed to be the safest antipyretic in paediatrics.